Agency and answerability selected essays - Watson, Gary, 1943- (Oxford : Clarendon, 2004)
Charting the progress of Watson's thought over three decades this collection of essays on human action examines such questions as: in what ways are we free and not free, rational and irrational, responsible or not for what we do?
Description based on print version record.
Includes bibliographical references and index.
Keywords: Agent (Philosophy); Free will and determinism